Attitudes and Behavior of Bangkok Residents regarding Reducing the Use of Plastic Bags - Lealaphan, Acharapan; Launglaor, Wisanu (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2014)
Plastic bags are artifacts formed to meet the needs of consumers. Consumers find them convenient in their daily life, especially when shopping. Using plastic bags means we are increasing the bulk of plastic waste in the world. Many countries around the world are aware of the problem of plastic waste and seriously try to find measures to reduce their use. Thailand uses 20 million tons of plastic bags per year, but there is no law seriously regulating the use of plastic bags as in many countries. There are only limited efforts by some government agencies stressing an awareness and recognition of the problems. However, those plastic waste campaigns do not seem practical. For this reason the researchers are interested in studying people’s attitudes and behaviors regarding reducing the use of plastic bags as well as reference group who influence the decisions and the self-control of the use of plastic bags. The results showed that people are aware of the projects reducing the use of plastic bags from newspapers, the internet and television. It was found that 55.00 percent of people are aware of the projects thought that the project was successful. The remaining 45.00 percent thought that the projects were not successful because of common habits, such as getting used to the use of plastic bags, the lack of conscience, and the thought of plastic bags as a necessity and convenience. Campaigns to seriously reduce the use of plastic bags are not continuous. Vendors still use plastic bag packaging, and there is a lack of support from the government.